2023
DOI: 10.1002/bab.2520
|View full text |Cite
|
Sign up to set email alerts
|

Identification of angiogenesis‐related subtypes, the development of a prognosis model, and features of tumor microenvironment in colon cancer

Feifei Wang,
Changjing Wang,
Baokun Li
et al.

Abstract: Angiogenesis is associated with tumor progression, prognosis, and treatment effect. However, the angiogenesis’ underlying mechanisms in the tumor microenvironment (TME) still remain unclear. Understanding the dynamic interactions between angiogenesis and TME in colon adenocarcinoma (COAD) is necessary. We downloaded the transcriptome data and corresponding clinical data of colon cancer patients from The Cancer Genome Atlas (TCGA) and the Gene Expression Omnibus (GEO) databases, respectively. We identified two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 67 publications
1
2
0
Order By: Relevance
“…However, minimal differences were noticed regarding EREG-mRNAsi, TMB, and the top 10 gene mutations. These findings align with previous research ( 14 , 15 ). Utilizing three machine learning algorithms, we identified four genes significantly associated with CRC subtypes.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, minimal differences were noticed regarding EREG-mRNAsi, TMB, and the top 10 gene mutations. These findings align with previous research ( 14 , 15 ). Utilizing three machine learning algorithms, we identified four genes significantly associated with CRC subtypes.…”
Section: Discussionsupporting
confidence: 93%
“…While previous studies have reported on the role of angiogenesis-related clusters in CRC ( 14 , 15 ), these studies lacked clinical samples and larger sample sizes of CRC datasets for gene expression verification. In contrast, our study utilized three machine learning algorithms to screen for important genes, resulting in a smaller but more accurate predictive set compared to previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation